Kepemimpinan Pendidikan Islam dalam Perspektif Etnis: Integrasi Kearifan Lokal dalam Konteks Indonesia - Winarti; Normuslim; Muslimah (Al-Mudarris, 2026)
This study aims to examine Islamic educational leadership in the context of ethnic diversity in Indonesia, with a focus on the integration of local wisdom values and Islamic leadership principles. The analytical focus of this study covers two aspects: (1) identifying the alignment of leadership values in the local cultures of the Nusantara with the principles of Islamic leadership, and (2) formulating an integrative, contextual, and relevant model of Islamic educational leadership within Indonesia’s multicultural society. Previous studies indicate that research on Islamic educational leadership remains dominated by normative approaches and has not yet systematically integrated local cultural dimensions into a comprehensive conceptual model, resulting in a gap in the development of leadership models grounded in local wisdom. This study employs a qualitative approach using library research. Data were obtained through the documentation of primary and secondary literature and analyzed using content analysis with a thematic approach to identify patterns, value relationships, and conceptual syntheses across sources. The research results indicate that local wisdom values such as consensus-based deliberation (musyawarah mufakat), mutual cooperation (gotong royong), social solidarity, and respect for customs align substantively with the Islamic principles of shura, amanah, justice, and ukhuwah. Based on this synthesis, an integrative Islamic educational leadership model rooted in the local wisdom of the Nusantara was developed, emphasizing contextual, inclusive, participatory, democratic, and adaptive leadership. This model strengthens social bonds, enhances the effectiveness of educational institution management, and reinforces the harmony between cultural identity and Islamic identity. This study recommends the further development of this model as a framework for strengthening the quality of leadership in Islamic educational institutions in Indonesia. Furthermore, the application of local wisdom in Islamic educational leadership can strengthen social relationships, improve the effectiveness of educational institution management, and reinforce cultural and Islamic identities in a harmonious manner. This study recommends the development of a model of Islamic educational leadership based on local wisdom to strengthen the quality of Islamic educational institutions in Indonesia.